Omentectomy for oncological surgical staging by transvaginal natural orifice transluminal endoscopic surgery (vNOTES): a preliminary study - Hurni, Yannick; Huber, Daniela (Frontiers in Surgery, 2023)
Objective: This study aimed to determine the feasibility of performing omentectomy by transvaginal natural orifice transluminal endoscopic surgery (vNOTES) for surgical staging of ovarian and highrisk endometrial malignancies.Methods: This descriptive study was realized in a non-university hospital in Switzerland. Eighteen patients with suspicious adnexal masses or high-risk endometrial cancer underwent surgical staging comprising infracolic omentectomy by vNOTES between May 2020 and April 2023.Results: Patients underwent oncological surgical staging for suspicious adnexal masses in 14 cases (77.8 %) and high-risk endometrial cancer in 4 cases (22.2 %). vNOTES omentectomies were performed in all patients without complications. Associated procedures included salpingooophorectomy (94.4 %), hysterectomy (55.6 %), peritoneal biopsies (33.3 %), pelvic sentinel lymph node biopsies (22.2 %), and appendectomy (5.6 %). The median time to perform omentectomies was 9 (4 -13) minutes. All oncological staging were completed by vNOTES. No significant intraoperative complications occurred. We observed 1 case (5.6 %) of postoperative fever probably associated with vaginal cuff infection (Clavien-Dindo grade II).This study demonstrated the feasibility of performing vNOTES oncological staging requiring complex extrapelvic procedures such as infracolic omentectomy, supporting its potential role for managing gynecological malignancies such as ovarian and high-risk endometrial cancers. However, before expanding this approach outside study settings, strong evidence of its feasibility, practical benefits, and long-term oncological outcomes are needed.